Two Arbuscular Mycorrhizal Fungi Alleviates Drought Stress and Improves Plant Growth in Cinnamomum migao Seedlings - Xiaofeng Liao; Jingzhong Chen; Ruiting Guan; Jiming Liu; Qinwen Sun (Mycobiology, 2021)
Cinnamomum migao plants often face different degrees of drought in karst habitats, which can lead to plants’ death, especially in the seedling stage. Widespread of arbuscular mycorrhizal (AM) fungi in karst soils have the potential to address this drought, which is a threat to C. migao seedlings. We inoculated C. migao seedlings with spores from Glomus lamellosum and Glomus etunicatum, two AM fungi widely distributed in karst soils, to observe seedling growth response after simulated drought. Our results showed that 40 g of G. lamellosum and G. etunicatum significantly promoted the growth of C. migao seedlings, 120 days after inoculation. Following a 15-day drought treatment, root colonization of the seedlings with G. lamellosum or G. etunicatum had lower the accumulation of malondialdehyde (MDA) and increased the accumulation of enzymes and osmotic substances in the seedlings. The relative water content in different organs (roots, stems, and leaves) of the drought-stressed seedlings was higher in plants with G. lamellosum or G. etunicatum than in plants without AM fungi colonization. Our results showed that inoculation with AM fungi was an effective means to improve the drought resistance of C. migao seedlings.